2015
DOI: 10.11114/jets.v4i2.1162
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Relationship between Eighth Grade Students’ Learning Styles and Attitudes towards Mathematics

Abstract: The aim of this research is to determine eighth grade students' learning styles and attitudes toward math class and to show the relationship between their learning styles and attitudes toward math class. Sample of the research consists of 100 eighth grade students having education in a school in the Central Anatolia of our country. As data collection tool, Kolb Learning Style Inventory and attitude scale toward math class. According to the data obtained, it has been seen that attitude level to math lesson of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
1
4
0
3
Order By: Relevance
“…The results of current study is consistent with the results of Sudira et al ( 2018) on the impact of Kolbs' learning styles for academic achievement of pre-service teachers, although in this study, learning styles had differences impacts based on the field of students. Besides, results of Aydin (2016) shows similar results to the current research.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of current study is consistent with the results of Sudira et al ( 2018) on the impact of Kolbs' learning styles for academic achievement of pre-service teachers, although in this study, learning styles had differences impacts based on the field of students. Besides, results of Aydin (2016) shows similar results to the current research.…”
Section: Discussionsupporting
confidence: 89%
“…The general features of these styles can be observed in Table 1. Researchers believe that if professors and planners pay attention to learning styles at various educational levels, it facilitates learning and educational processes and helps learners to become more efficient in choosing the course and occupational situations (Sudira et al, 2018;Aydin, 2016). Villanueva (2020) believes that cognitive styles are used to enhance learning and there are use recommended to be used in educational circumestance.…”
Section: Cognitive Learning Stylesmentioning
confidence: 99%
“…There was a predominance of diverging learning style across all years of the program. Liew et al [11], reported that there was no gender differences in learning style.However, studies have reported relation between learning style and gender of students [12,13].The difference in the findings related to gender can be associated to the context of cultures, as majority of the study participants were females and females probably tend to learn through feelings [13].…”
Section: An Exploration Of the Learning Style Among Undergraduate Nurmentioning
confidence: 88%
“…The current importance of mathematics and science makes it imperative to understand student affective dispositions towards these subjects. Research on attitudes towards science (e.g., Osborne, Simon, & Collins, 2003) and mathematics (e.g., Aydin, 2016) is thus needed. Assessment of these attitudes require culturally appropriate instruments in the language of the studied population (Minner, Ericson, Wu, & Martinez, 2012).…”
Section: Introductionmentioning
confidence: 99%